Qiro'ah Mubadalah and the Development of Feminism Discourse: Faqihuddin Abdul Kodir's Perspective - Akbar, Yogi Muhammad; Mufidah (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The study of qiro'ah Mubadala and the development of the discourse on feminism is important to discuss because this theme is a topic that is quite often discussed by the public with various problems that arise due to a lack of understanding of feminism, so here the researcher tries to explain how the concept of qiro'ah Mubadala and the discourse of feminism from the perspective of Faqihuddin Abdul Kodir as one of the figures who wrote a lot about gender. The purpose of this research is so that readers can find out how the concept of qiro'ah mubadalah and the development of feminist discourse from Faqihuddin Abdul Kodir's perspective. The method used in this research is based entirely on a literature review or what is commonly referred to as a literature study. What is meant by literature review is a review carried out to overcome a problem that depends on basic investigations and on the data that has been collected The results are 1) Qira'ah Mubadalah according to Faqihuddin is a method of approach to interpreting Islamic source texts, both the Qur'an and hadith with the perspective of equality between men and women.2) the position and men and women are seen as needing each other so that there is no patriarchal practice in the relations between men and women. Keywords: Qiro’ah Mubadalah, Feminism, Faqihuddin Abdul Kodir